A Quasi-Experimental Analysis of Schoolwide Violence Prevention Programs. (2nd January 2017) - Barnes, Tia Navelene; Leite, Walter; Smith, Stephen W.
Abstract : Violence prevention programs are commonplace in today's schools, though reviews of the literature reveal mixed empirical findings on their effectiveness. Often, these programs include a variety of components such as social skills training, student mentoring, and activities designed to build a sense of school community that have not been tested for individual effectiveness. To fill this gap, we wanted to determine the relationships between specific violence prevention program components and aggression and violence outcomes. Using the U.S. Department of Education's School Survey on Crime and Safety, we estimated the effects of components of violence prevention programs through analyses with proportional odds logistic regression and Poisson regression models. We found significant relationships between three violence prevention program components (individual attention, mentoring, tutoring, and/or coaching; recreational, enrichment, or leisure activities; and involving students in resolving student conduct problems) and aggression and violence outcomes.